A multifunctional switched-capacitor programmable gain amplifier for high-definition video analog front-ends*Project supported by the National Natural Science Foundation of China (No. 61106027), and the Science and Technology Project of Shanxi Province (No. 2014K05-14). (March 2015) - Zhang, Hong; Zhang, Jie; Zhang, Mudan; Li, Xue; Cheng, Jun
Abstract A multifunctional programmable gain amplifier (PGA) that provides gain and offset adjusting abilities for high-definition video analog front-ends (AFE) is presented. With a switched-capacitor structure, the PGA also acts as a sample and holder of the analog-to-digital converter (ADC) in the AFE to reduce the power consumption and chip area of the whole AFE. Furthermore, the PGA converts the single-ended video signal into differential signal for the following ADC to reject common-mode noise and interferences. The 9-bit digital-to-analog converter (DAC) for gain and offset adjusting is embedded into the switched capacitor networks of the PGA. A video AFE integrated circuit based on the proposed PGA is fabricated in a 0.18-μm process. Simulation and measurement results show that the PGA achieves a gain control range of 0.90 to 2.34 and an offset control range of −220 to 220 mV while consuming 10.1 mA from a 1.8 V power supply.